A Designed TiO2/Carbon Nanocomposite as a High‐Efficiency Lithium‐Ion Battery Anode and Photocatalyst. Issue 42 (27th August 2015) - Peng, Liang; Zhang, Huijuan; Bai, Yuanjuan; Feng, Yangyang; Wang, Yu
Abstract Herein, a peapod‐like TiO2/carbon nanocomposite has successfully been synthesized by a rational method for the first time. The novel nanostructure exhibits a distinct feature of TiO2 nanoparticles encapsulated inside and the carbon fiber coating outside. In the synthetic process, H2Ti3O7 nanotubes serve as precursors and templates, and glucose molecules act as the green carbon source. With the alliciency of hydrogen bonding between H2Ti3O7 and glucose, a thin polymer layer is hydrothermally assembled and subsequently converted into carbon fibers through calcinations under an inert atmosphere. Meanwhile, the precursors of H2Ti3O7 nanotubes are transformed into the TiO2 nanoparticles encapsulated in carbon fibers. The achieved unique nanocomposites can be used as excellent anode materials in lithium‐ion batteries (LIBs) and photocatalytic reagents in the degradation of rhodamine B. Due to the synergistic effect derived from TiO2 nanoparticles and carbon fibers, the obtained peapod‐like TiO2/carbon cannot only deliver a high specific capacity of 160 mAh g−1 over 500 cycles in LIBs, but also perform a much faster photodegradation rate than bare TiO2 and P25. Furthermore, owing to the low cost, environmental friendliness as well as abundant source, this novel TiO2/carbon nanocomposite will have a great potential to be extended to other application fields, such as specific catalysis, gas sensing, and photovoltaics.